Case report: Effect of Hb E heterozygosity on HbA1c value by the Tosoh HLC-723G11 - Gao, Wei; Li, Wenyu; Zheng, Qian; Jiang, Nenggang; Tang, Huairong (Frontiers in Public Health, 2023)
Objective: We report the effect of Hb E heterozygosity on HbA1c value by the Tosoh HLC-723G11.A 45-year-old Chinese woman presented with an abnormally low HbA1c level of 3.7% (3.9-6.1%) in a health examination. Fasting blood glucose was normal. Blood routine examination and serum bilirubin were in the normal range. HbA1c was determined by TOSOH HLC-723G11. There was an abnormal peak between A1c and A0 on the chromatogram. Hemoglobin electrophoresis indicated that the Hb E zone accounted for 25.1%. The β-thalassemia-related genes (mutant type) were βE M/N, and the related gene CD26 (A > G) was mutated. OGTT indicated prediabetes.Conclusion: Hb E heterozygosity may reduce HbA1c value with abnormal chromatograms, as determined by a Tosoh HLC G11 analyzer. The Tosoh HLC G11 analyzer can well identify Hb E variation. In this case, further blood glucose-related tests should be performed to avoid missed diagnoses. However, a large sample size is needed to confirm this conclusion.